The Lived Experience of Responsible Leadership: A Transcendental Phenomenological Study of Five Middle School Teachers - MacTaggart, Ryan W.; Lynham, Susan A. (Journal of Leadership, Accountability and Ethics, 2019)
Limited research exists at the intersection of Responsible Leadership (RL) and education organizations. The purpose of this transcendental phenomenological study was to describe the essence of a Responsible Leadership experience from the perspective of middle school teachers in the western United States. Five participants who were all active middle school educators participated in in-depth interviews about their experiences based on the 3Es of Responsible Leadership: effectiveness, ethics, and endurance. Ten shared textural descriptions of experience were constructed from the data: diligence; open RL to more people; dedication to development; take ownership; genuine care for teachers; consistency; fortitude; guided by vision and values; and desirable outcomes of RL for teachers. Implications for future research and practice are addressed.